Explanation of Security Sequences of Climate Change (Case Study: Iran’s Central Drainage Basin) - Morad Kavianirad; Yadollah Karimi Pour; Hedayat Fahmi; Sadegh Karami (تحقیقات کاربردی علوم جغرافیایی)
Efforts to provide security have always been of great importance to human being. In recent decades, the security issues of climate change have attracted attentions due to its sustainable consequences on the lives and civilization of humans. Among all countries, the ones which are placed in draught belt, like our country Iran, have hurt a lot because of low precipitations and also mismanagements in water resources control. Climate change show itself by changes in precipitation patterns, reduction of precipitation and increasing of temperature. According to the present data, Iran's central drainage basin which consists of important geopolitical provinces, has been affected by the above mentioned factors. This descriptive-analytic research is carried out based on the effects of climate change on Iran's central basin which provides approximately 48 percent of Iran’s GDP.  Continuity of climate changes in this region can make critical problems in social, environmental, economic and political scales and the lives of the citizens would be affected as well. To conclude, the persistence of the current conditions in climate change in the central drainage basin of Iran, would result in challenges through the national stability and security.